Long-term Terrestrial Water Budget Estimates Over the Middle East North Africa (MENA) Region - Nisa, Zaib Un; Govind, Ajit (CGIAR FOCUS Climate Security, 2022)
Water security is a central challenge for the Middle East and North Africa (MENA) region that renders water budgeting significantly important. To carefully use water resources, the region needs to understand the behaviour, patterns, and responses of its water-dependent systems. To this end, this study employs the water accounting approach and investigates average trends of climatic water availability in the MENA region.